Updating Animal Welfare Thinking: Moving beyond the 'Five Freedoms' towards 'A Life Worth Living' - Mellor DJ (Massey University)
Gaining knowledge of animal welfare and applying it in ways that improve our care of animals can be understood as a journey. Different countries, regions of countries and people within those countries have reached different stages in this journey. However, even for those who have travelled far on this journey, it will never end because new or modified approaches to animal care will be needed as we continue to learn more about how animals perceive and respond to the circumstances in which they find themselves.